Kajian Lafal Yang Dii'tibarkan Dengan Kekuatan Makna Dari Dalil-Dalilnya (Al-Lafzubi I'tibari Quwwati Dilalatihi 'Ala Al-Ma'na) Zhahir Dalalah (Zhahir Dan Nash) - Muhammad Fachmi; Sardiyanah (IAI Muhammadiyah Sinjai, 2022)
This study aims to examine the pronunciation that is implied by the strength of the meaning of the arguments. The research method used is the library research method. The data collection method used is the method of observation and documentation. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent misinformation in data analysis, inter-library checks and re-reading of the literature, as well as attention to the supervisor's comments, are carried out. The results of this study are the elaboration of the theoretical basis and practice of counselling as a whole including 1) Mujetahid's opinion about ijtihad, 2) The concept of zahir and nash pronunciation, 3) the concept and purpose of zahir and texts, 4) Ulama about the existence of zahir and texts, 5) results of research on zahir and nash